User’s Continuance Intentions of Digital Payment Based on Expectation-Confirmation Method and Trust - Shofia, Alima (Prodi Akuntansi FEBM Universitas Maritim Raja Ali Haji, 2024)
Since the Covid-19 pandemic entered Indonesia in 2020, people have started to switch from cash/traditional payments to digital payments with aim to reduce direct physical contact. Digital payment that currently booming is Qris payment method, which offer convenience and speed in transactions. This study aims to look at user continuance intention on using digital payments using the Expectation-Confirmation Model (ECM) approach. In this volatility, uncertainty, complexity, and ambiguity (VUCA) era, this study adapt the concept of trust in technology adoption. Based on the literature study that has been collected, researchers obtain several variables that can influence user intentions to continue using digital payments, including: confirmation, perceived usefulness, satisfaction, information quality, perceived privacy protection and security, trust, and continuance intention.